Steppe Eagle breeding population surveys in Turkey between 2015 and 2022 - Márton Horváth; Tibor Juhász; István Béres; Cansu Özcan; Burak Tatar; Ömral Ü. Özkoç; Süreyya İsfendiyaroğlu; Matthias Schmidt; Igor V. Karyakin (Пернатые хищники и их охрана)
The status of the Steppe Eagle (Aquila nipalensis) was unclear in Turkey, which forms the south-western border of the species’ breeding distribution. The status of the species in Turkey has never been clear, as historically only two nesting sites were found and documented in the wider area of Tuz Gölü, which were proved to be active only in some years between 1969 and 1980. One nest site in Tuz Gölü was found in some years between 1969 and 1975, while another nest was found in Bolluk Gölü in 1975, and was active also in 1980. There were no published breeding records since 1980 until 2003, when a Steppe Eagle brood was found accidentally in central Anatolia by Hungarian birdwatchers. There were no other published breeding records of Steppe Eagles in Turkey in the twentieth century, although adult birds have been observed in a few occasions in Central and Eastern Anatolia during the breeding season between 1998 and 2015.